TradingView دور التكنولوجيا المالية في التداول والاستثمار- دراسة حالة منصة - رضوان، عادل; جديدي، موسى (University Of Eloued جامعة الوادي, 2024)
تهدف هذه الورقة البحثية إلى ابراز دور التكنولوجيا المالية في تسهيل عملية التداول والاستثمار في الأسواق المالية. وتُعد منصة Trading View مثالاً بارزاً من برامج التكنولوجيا المالية، حيث تقدم مجموعة من الأدوات المتقدمة لتحليل الأسواق المالية. وقد تم استخدام دراسة حالة وأمثلة تطبيقية لإظهار كيفية تحديد نقاط الدخول والخروج باستخدام مؤشرات فنية مثل المتوسطات المتحركة ومؤشر القوة النسبية (RSI). وتقييم مستويات الدعم والمقاومة لتحليل تحركات الأسعار واتخاذ قرارات الشراء أو البيع. وإعداد تنبيهات التداول لتلقي إشعارات فورية عند تحقيق شروط استثمارية معينة. واختبار الاستراتيجيات الاستثمارية عبر أدوات الباك تيست التي تقدم تحليلاً تاريخياً للأداء. والاستفادة من مجتمع المستثمرين بمشاركة الأفكار والتحليلات. وقد خلصت الدراسة إلى أن هذه الأدوات تدعم المستثمرين في إدارة المخاطر، تحسين استراتيجياتهم، واكتساب رؤى عميقة حول الأسواق المالية. حيث توفر منصة TradingView بيئة شاملة للتحليل التفاعلي الذي يُمكّن من اتخاذ قرارات استثمارية أكثر دقة وفعالية. Abstract: This research paper aims to highlight the role of financial technology in facilitating trading and investment in financial markets. Trading View is a prominent example of financial technology platforms, offering a range of advanced tools for market analysis. A case study and practical examples were used to demonstrate how to identify entry and exit points using technical indicators such as moving averages and the Relative Strength Index (RSI). The study also evaluates support and resistance levels to analyze price movements and make buy or sell decisions, sets up trading alerts to receive instant notifications when specific investment conditions are met, and tests investment strategies through back testing tools that provide historical performance analysis. Additionally, it explores the benefits of engaging with the investor community by sharing ideas and analyses. The study concluded that these tools support investors in risk management, improving their strategies, and gaining deeper insights into financial markets. Trading View provides a comprehensive environment for interactive analysis, enabling more precise and effective investment decisions.
The Role of FinTech in Trading and Investing - A Case Study of Trading View
مداخلة
Keywords: التكنولوجيا المالية; التداول; الاستثمار; الأسواق المالية; TradingView; المؤشرات الفنية; Financial technology; trading; investment; financial markets; technical indicators